O teatrze science fiction kilka uwag - Marek Dybizbański (Przestrzenie Teorii)
The science fiction aesthetics has actually never created (formed) its own kind of drama and in spite of attempts undertaken several times it has not been feeling completely at home. Theoreticians (Theorists) of science fiction see the theatre as an inconvenient (troublesome) partner which "reveals the imitative character of the presented world and destroys the atmosphere of fantasticality". In the meantime the history of the science fiction drama reveals quite an astonishing regularity, namely it appears that the manner of creation of the science fiction stage illusion is completely independent of the degree of technical advancement of the theatrical machinery. The better the equipment of the theatre, the more modestly science fiction appears in it. Coexistence of fantasticality and theatricality in the works written for stage, however, does not occur without any conflict and is more often based on respecting of limitations (restrictions) resulting from the system rather than harmonious co-operation.